2015
DOI: 10.1590/1981-863720150003000022935
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of color variation of restorative materials used on pediatric dentistry after pigmentation

Abstract: ObjectiveTo quantify the color variation of two glass ionomer cements and a composite resin used in pediatric dentistry, after being immersed in different pigments agents. (Ketac™ Molar and Photac™ Fil) Methods Using two glass ionomer cements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In the study of Lopes et al 36 in which they examined the coloring e ect of children's beverages on restorative materials, they reported that ice tea caused the most coloring among the coloring agents, similar to the results of the current study. e ΔE values in the crowns tested in our study were ordered as ice tea > cherry juice > cola > orange juice > chocolate milk > distilled water.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In the study of Lopes et al 36 in which they examined the coloring e ect of children's beverages on restorative materials, they reported that ice tea caused the most coloring among the coloring agents, similar to the results of the current study. e ΔE values in the crowns tested in our study were ordered as ice tea > cherry juice > cola > orange juice > chocolate milk > distilled water.…”
Section: Discussionsupporting
confidence: 85%
“…Tunç et al 23 , in their study examining the sensitivity of di erent restorative materials to coloration, explained that chocolate milk caused less coloration than other beverages, and this was due to the di erence in pH values of the beverages evaluated. Similarly, in the study of Lopes et al 36 , it was proven that chocolate milk has the lowest coloring e ect of all the materials examined. In the results of the present study, supporting the results of other studies, it was observed that chocolate milk caused the least coloration among all the evaluated beverages and this coloration was at a clinically acceptable level.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations